2017
DOI: 10.1111/aor.13056
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Validation of a Less Invasive Gastrostimulator

Abstract: Gastrointestinal stimulator implants have recently shown promising results in helping obese patients lose weight. However, to place the implant, the patient currently needs to undergo an invasive surgical procedure. We report a less invasive procedure to stimulate the stomach with a gastrostimulator. After attempting fully endoscopic implantation, we more recently focused on a single incision percutaneous procedure. In both cases, the challenges in electronic design of the implant are largely similar. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The anchor is intended to be placed in a less‐invasive way through single incision percutaneous access with a single step release, 33 with (1) the summarized procedure and (2) the tool illustrated in Figure 1B. The IGS is encapsulated in medical‐grade silicone rubber 34 that was previously validated in vivo by our team 35 . The IGS delivers biphasic square current pulses from 0.5 to 15.0 mA, with a width of 0.2 to 32.0 ms, at a frequency of 20 Hz to 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anchor is intended to be placed in a less‐invasive way through single incision percutaneous access with a single step release, 33 with (1) the summarized procedure and (2) the tool illustrated in Figure 1B. The IGS is encapsulated in medical‐grade silicone rubber 34 that was previously validated in vivo by our team 35 . The IGS delivers biphasic square current pulses from 0.5 to 15.0 mA, with a width of 0.2 to 32.0 ms, at a frequency of 20 Hz to 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…The IGS is encapsulated in medicalgrade silicone rubber 34 that was previously validated in vivo by our team. 35 The IGS delivers biphasic square current pulses from 0.5 to 15.0 mA, with a width of 0.2 to 32.0 ms, at a frequency of 20 Hz to 1 kHz. Under the use case described in the experimental protocol section, the battery is expected to last a few days to a few weeks without being charged, depending on the delivered stimulation energy.…”
Section: Implantable Gastric Stimulation Devicementioning
confidence: 99%
“…Leslie's soup is a mixture of 0.5 wt% detergent (Teepol-L, Teepol Products, Kent, United Kingdom), and 25 wt% trisodium phosphate (anhydrous, 13438, Alfa Aesar, Heysham, United Kingdom), in de-ionized water. Cleanliness before encapsulation is essential for the survival of long-term implants (Vanhoestenberghe and Donaldson, 2013;Lonys et al, 2017;Kiele et al, 2020). Following rinsing, the conductivity of the rinse solution was monitored to confirm adequate cleanliness.…”
Section: Implant Packaging and Encapsulationmentioning
confidence: 99%
“…Lonys et al of the Université Libre de Bruxelles, Brussels, Belgium reported on gastrointestinal stimulator implants that have been shown promising in helping obese patients lose weight. They developed a less invasive procedure to stimulate the stomach by creating a single incision percutaneous procedure.…”
Section: Functional Electrical Stimulation and Musculoskeletal Supportmentioning
confidence: 99%